Numerical analysis of aerosol effects on a heavy precipitation event in Beijing - Yanqing ZHANG; Yi GAO; Liren XU; Meigen ZHANG (暴雨灾害)
Anthropogenic aerosols have an important impact on summer heavy precipitation, but their impact and associated mechanisms are still greatly uncertain. In this study, the WRF-Chem including the aerosol-meteorology interactions was used to investigate the effects and possible mechanisms of aerosol direct, indirect, and total effects on a heavy rainfall event that occurred in Beijing during August 12—13, 2020. The results are as follows. (1) In the first stage of the precipitation (15∶00—18∶00 BT on August 12), due to the aerosol effects on solar radiation and cloud nuclei, the aerosol direct, indirect, and total effects all decrease the hourly precipitation intensity in the Beijing urban area, with a maximum reduction of 6 mm·h-1, 1 mm·h-1, and 4 mm·h-1, respectively. (2) In the second stage (20∶00 BT on August 12 to 04∶00 BT on August 13), both aerosol direct and indirect effects decrease the hourly precipitation intensity, with a maximum reduction of about 4 mm·h-1. The aerosol total effect has little impact on the hourly precipitation intensity but delays the precipitation time. Generally, the aerosol direct effect enhances the warm cloud process while weakening the cold cloud process, thus decreasing the precipitation and advancing the strong precipitation process in the second precipitation stage. The aerosol indirect effect decreases the effective radius of rain, thereby reducing the merging process and precipitation, and delaying the onset of heavy precipitation during the second precipitation stage. The aerosol total effect on precipitation is a nonlinear result of both aerosol direct and indirect effects, with the direct effect dominating in the first stage of precipitation and the indirect effect dominating in the second stage of precipitation.